Examining the processes involved in the design of journalistic information graphics: an exploratory study. Issue 2 (3rd April 2017) - Barnes, Spencer R.
Abstract: Journalism students aspiring to become designers and graphics editors within the American news industry are routinely trained to produce information graphics (infographics) but to date there has been a very little exploration into what the infographic design process entails. This paper attempts to articulate the process and investigate where strengths and fallacies potentially exist in its execution. A cognitive task analysis was employed to understand the experiences of 10 participants tasked with individually designing an infographic using complimentary data sets. Results indicate that the infographic design process is macrocognitive and that when a sufficient level of expertise exists an individual's conceptualization of the process is more congruent to their application of it, and that the process deserves further attention from researchers.